Management of chronic immune thrombocytopenic purpura: targeting insufficient megakaryopoiesis as a novel therapeutic principle - Rank, Andreas (Dove Medical Press, 2010)
Traditionally, anti-platelet autoantibodies accelerating platelet clearance from the peripheral circulation have been recognized as the primary pathopysiological mechanism in chronic immune thrombocytopenia (ITP). Recently, increasing evidence supports the co-existence of insufficient megakaryopoiesis. Inadequate low thrombopoietin (TPO) levels are associated with insufficient proliferation and differentiation of megakaryocytes, decreased proplatelet formation, and subsequent platelet release. Recently two novel activators of TPO receptors have been made available: romiplostim and eltrombopag. In several phase III studies, both agents demonstrated increase of platelet counts in about 80% of chronic ITP patients within 2 to 3 weeks. These agents substantially broaden the therapeutic options for patients with chronic ITP although long-term results are still pending. This review will provide an update on the current conception of underlying mechanisms in ITP and novel, pathophysiologically based treatment options.